Cryopreservation alters the immune characteristics of platelets. Issue 12 (12th October 2021) - Wood, Ben; Padula, Matthew P.; Marks, Denese C.; Johnson, Lacey
Abstract: Background: Cryopreserved platelets are under clinical evaluation as they offer improvements in shelf‐life and potentially hemostatic effectiveness. However, the effect of cryopreservation on characteristics related to the immune function of platelets has not been examined. Study Design and Methods: Buffy coat derived platelets were cryopreserved at −80°C using 5%–6% dimethylsulfoxide (DMSO, n = 8). Paired testing was conducted pre‐freeze (PF), post‐thaw (PT0), and after 24 h of post‐thaw storage at room temperature (PT24). The concentration of biological response modifiers (BRMs) in the supernatant was measured using commercial ELISAs and surface receptor abundance was assessed by flow cytometry. Results: Cryopreservation resulted in increased RANTES, PF4, and C3a but decreased IL‐1β, OX40L, IL‐13, IL‐27, CD40L, and C5a concentrations in the supernatant, compared to PF samples. C4a, endocan, and HMGB1 concentrations were similar between the PF and PT0 groups. The abundance of surface‐expressed P‐selectin, siglec‐7, TLR3, TLR7, and TLR9 was increased PT0; while CD40, CLEC2, ICAM‐2, and MHC‐I were decreased, compared to PF. The surface abundance of CD40L, B7‐2, DC‐SIGN, HCAM, TLR1, TLR2, TLR4, and TLR6 was unchanged by cryopreservation. Following 24 h of post‐thaw storage, all immune associated receptors and TLRs increased to levels higher than observed on PF and PT0 platelets. Conclusion: Cryopreservation alters the immune phenotype of platelets. Understanding the clinical implications of the observed changes in BRM release and receptor abundance are essential, as they may influence the likelihood of adverse events.